Sensory and immune genes identification and analysis in a widely used parasitoid wasp Trichogramma dendrolimi (Hymenoptera: Trichogrammatidae). (11th May 2016) - Zhang, Su‐Fang; Kong, Xiang‐Bo; Wang, Hong‐Bin; Zhou, Gang; Yu, Jin‐Xiu; Liu, Fu; Zhang, Zhen
Abstract: Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae) is one of the preponderant egg parasitoids of Dendrolimus spp., which are important defoliators of coniferous forests. This parasitoid wasp has been widely released to control pine caterpillar and other lepidopteran pests, but its control efficiency needs to be improved. Sensory systems are crucial for T. dendrolimi to locate hosts, and immunity is probably involved after egg deposition in the host cavity; however, few reports have focused on the molecular mechanism of olfactory detection and survival of T. dendrolimi . It is necessary to identify these genes before further functional research is conducted. In this study, we assembled and analyzed the transcriptome of T. dendrolimi using next‐generation sequencing technology. The sequencing and assembly resulted in 38 565 contigs with N50 of 3422 bp. Sequence comparison indicate that T. dendrolimi sequences are very similar to those of another parasitoid Nasonia vitripennis . Then the olfactory, vision, and immune‐related gene families were identified, and phylogenetic analyses were performed with these genes from T. dendrolimi and other model insect species. Furthermore, phylogenetic tree with odorant binding proteins of T. dendrolimi and their host Dendrolimus was constructed to determine whether convergent evolution exists. These genes can be valid targets for further gene function research. The present study may help us to understand host location and survival mechanisms of T. dendrolimi and to use them more efficiently for pest control in the future.